The expansion of the urban perimeter of Londrina-Pr combined with the peripheral construction of housing complexes: in search of a sustainable development - Bertini, Isabelle Teixeira; Antonello, Ideni Terezinha (National Journal of City Management, 2023)
Under the dominance of the capitalist system, cities follow the logic of the market, since the interests of the most varied agents, such as land and real estate producers, with the consent of the State, determine the social production of urban space, a reality that can be found in the city of Londrina-PR. In this context, the objective of this article was to present what is - and if it exists - sustainability in the expansion of the urban perimeter of the city of Londrina-PR, having as a parameter the construction of housing complexes in peripheral areas of the city. To achieve this objective, the dialectic was used as a guiding paradigm, based on the document analysis method. It is concluded that despite being considered a relatively young city, Londrina-Pr was - and continues to be - the stage of an accelerated and disorderly territorial and population growth, where the construction of housing complexes contributed to the increase of the city's territorial area, placing in motion real estate speculation due to the emergence of large urban voids. This reality contributes to the perpetuation of a segregationist logic, where a large part of the population does not have access to basic infrastructure, demonstrating that the city does not have a sustainable development aimed at the quality of life of the population. There is an urgent need to change this reality.